Beyond men and women: a critical perspective on gender and disaster. Issue 3 (22nd September 2016) - Gaillard, J.C.; Sanz, Kristinne; Balgos, Benigno C.; Dalisay, Soledad Natalia M.; Gorman‐Murray, Andrew; Smith, Fagalua; Toelupe, Vaito'a
Abstract : Consideration of gender in the disaster sphere has centred almost exclusively on the vulnerability and capacities of women. This trend stems from a polarised Western understanding of gender as a binary concept of man—woman. Such an approach also mirrors the dominant framing of disasters and disaster risk reduction (DRR), emphasising Western standards and practices to the detriment of local, non‐Western identities and experiences. This paper argues that the man—woman dichotomy is an insufficient construct with which to address the gendered dimensions of a disaster as it fails to capture the realities of diverse gender minorities in non‐Western contexts. The paper presents case studies from the Philippines, Indonesia, and Samoa, where gender minorities display specific patterns of vulnerability associated with their marginal positions in society, yet, importantly, also possess a wide array of endogenous capacities. Recognition of these differences, needs, skills, and unique resources is essential to moving towards inclusive and gender‐sensitive DRR.